The Effect Of Strategic Intelligence On Entrepreneurial Success: A Field Study Of The Opinions Of A Sample Of Scientific And Administrative Leaders In The Private University Colleges In The Governorates Of Babylon And Holy Karbala - Zahir Salman Al-Janabi, Rana (Iraqi Journal for Administrative Sciences, 2024)
The research aims to demonstrate the impact of strategic intelligence in its dimensions (foresight, systemic thinking, future vision, partnership, and motivation) in pioneering success in its dimensions (financial dimension (profitability), pioneering satisfaction, sense of gratitude, pioneering preparedness), and the importance of research is reflected in the presentation of the most important treatments and proposals for the management of research organizations and put them into practice and benefit from them in order to improve the reality of their performance, and the problem of research was the question of the extent to which the departments of the colleges are interested in applying the dimensions of strategic intelligence and what is related to achieving the dimensions of strategic intelligence and what is related to achieving The research community included (7) civil colleges and universities in the holy provinces of Babylon and Karbala, and the research sample included a group of scientific and administrative leaders (113) leaders and distributed a questionnaire form to them, and the research relied on the use of a number of statistical methods available in statistical programs (Spss,v.23; Microsoft Excel,2010 ; Amos;v.23), the research found that strategic intelligence is the basic basis for building any strong organization capable of achieving success by several basic criterion that reflects the success of any organization.